Analysis of Skill Development in Throwing Placement for Indonesian National Boccia Athletes Through Structured Drill Training - Riyadi, Muhamad Bram; Nuryadin, Islahuzzaman; Ardhiyanto, Yanuar Dhuma; Wijaya, Febri; Demirci, Nevzat (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Boccia is a sport for athletes with cerebral palsy that requires high accuracy and consistency. The ability to place the ball as close as possible to the jack is the main measure of victory. This study aims to analyse the impact of applying structured drill training methods on improving the ball placement skills of Indonesian national Boccia athletes on the left and right targets. The research method used a quasi-experimental design with a pre-test and post-test single group design and a repeated measures design. The research sample consisted of 10 elite Indonesian national Boccia athletes who were preparing for international championships. Data collection tools were carried out using a Boccia ball throwing skill test on athletes with cerebral palsy. The data were analysed using IBM SPSS Statistics 27 software with repeated ANOVA tests. The results of the tests in the subject effects table showed differences in the pre-test and post-test mean data for ball placement skills on the jack on the left and right targets, with a sig. value of p<0.05. These results indicate that Boccia athletes were able to place the ball on the jack accurately and consistently after the intervention. From these results, it was concluded that structured drill training was effective in improving ball placement skills on the jack in Indonesian national Boccia athletes. These findings provide practical guidance for coaches in designing periodic training programs and for future researchers to integrate psychological factors such as competition anxiety into training interventions